Spiral bit-map signature for content-based images retrieval - Wang, Hui Hui (Faculty of Computer Science and Information Technology, 2003)
Images are generated in many application areas such as image processing, multimedia, digital libraries, remote sensing, astronomy, database applications and other related area at a fast rate. A content-based image retrieval (CBIR) systems needs to provide an effective and efficient access to image databases, based on visual content which includes colour, shape, texture and spatial features.